Manufacturing and Characterization of Three-Axis Magnetic Sensors Using the Standard 180 nm CMOS Technology - Chi-Han Wu (MDPI AG, 2021)
A three-axis micro magnetic sensor (MS) is developed based on the standard 180 nm complementary metal oxide semiconductor (CMOS) technology. The MS designs two magnetic sensing elements (MSEs), which consists of an x/y-MSE and an z-MSE, to reduce cross-sensitivity. The x/y-MSE is constructed by an x-MSE and an y-MSE that are respectively employed to detect in the x- and y-direction magnetic field (MF). The z-MSE is used to sense in the z-direction MF. The x/y-MSE, which is constructed by two magnetotransistors, designs four additional collectors that are employed to increase the sensing current and to enhance the sensitivity of the MS. The Sentaurus TCAD software simulates the characteristic of the MS. The measured results reveal that the MS sensitivity is 534 mV/T in the x-direction MF, 525 mV/T in the y-direction MF and 119 mV/T in the z-axis MF.